The influence of moisture content on the heat affected zone and the resulting in-plane shear strength of laser cut thermoplastic CFRP. (May 2015) - Staehr, R.; Bluemel, S.; Hansen, P.; Jaeschke, P.; Suttmann, O.; Overmeyer, L.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper investigations on the effect of the moisture content of thermoplastic CFRP on the laser induced heat affected zone (HAZ) and the resulting in-plane shear properties are presented. For this purpose carbon fibre reinforced polyetherimide (PEI) and polyphenylene sulphide (PPS) sheets were conditioned to different moisture contents and were then used for laser machining test specimens with contour and multipass cutting strategies. The extents of the HAZ were measured and in-plane shear tests were performed, revealing that the shear properties decrease when cutting material with high moisture content. This behaviour can be correlated with the type of HAZ which contains porosity caused by the vapourisation of water.